2019
DOI: 10.2169/internalmedicine.3129-19
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Primary Mediastinal Large B-cell Lymphoma during Pregnancy

Abstract: We experienced a pregnant woman with superior vena cava syndrome at 15 weeks of pregnancy who was diagnosed with primary mediastinal large B-cell lymphoma and given chemotherapy. In this case, the clinical courses of both the mother and infant were favorable without any serious complications because of close multidisciplinary cooperation. Based on a retrospective review of this case, the administration of CHOP-like regimens during the second and third trimesters appears relatively safe. Because pregnancy and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…One study on the pharmacokinetics of doxorubicin in pregnant women indicated a decreased clearance of doxorubicin during pregnancy [ 122 ]. According to several case reports, the use of doxorubicin appears relatively safe during pregnancy [ 105 , 123 , 124 , 125 , 126 ]. In contrast, a case of intrauterine death after exposure to epirubicin for breast cancer has been reported [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study on the pharmacokinetics of doxorubicin in pregnant women indicated a decreased clearance of doxorubicin during pregnancy [ 122 ]. According to several case reports, the use of doxorubicin appears relatively safe during pregnancy [ 105 , 123 , 124 , 125 , 126 ]. In contrast, a case of intrauterine death after exposure to epirubicin for breast cancer has been reported [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…7 There are reports of patients with PMBCL treated with R-CHOP during pregnancy and then transitioning to DA-REPOCH postpartum. 8 This was done due to the concern that etoposide would cause fetal cranial abnormalities and skeletal malformations. However, etoposide exposure during the second and third trimesters did not seem to cause any congenital malformations.…”
mentioning
confidence: 99%